Breaking the Culture of Violence against Civilians – A Case Study of Nigeria - Okonkwo , Nkiruka Stella (Corpus Intellectual, 2023)
Violence is seen as an intricate part of the Nigerian socio-political landscape, and often occurs in many ways including violent events targeting civilians which form the base for this study. Though the phenomenon of violence against civilians has found its way into many academic and developmental discourses, durable and practical solutions have not been fully implemented to effectively address its causes and consequences. The study has four objectives: to understand the concept of breaking the culture of violence against civilians; to determine effects of sexual violence against civilians; to examine effects of attacks against civilians; and to evaluate the effects of abduction or forced disappearance of civilians in Nigeria’. Relying on a methodical examination of existing scholarly works and secondary quantitative data generated from the database of the Armed Conflict Location & Event Data Project (ACLED) from January 1997 to September 2023, this study argues that violent events targeting civilian populations gave rise to a culture in Nigeria which requires urgent and collaborative actions for combating it. The People- Centered Development Theory is used as a theory to underscore the importance of engaging members of the community in efforts to prevent and mitigate violence against civilians in Nigeria. It was concluded that sexual violence, attacks and abduction/forced disappearance have significant effects on civilians and also on sustainable national development. Consequently, the study encourages the Nigerian government to urgently adopt and implement the Draft National Policy on Protection of Civilian and Civilian Harm Mitigation in Armed Conflict using a people-centered development approach as well as adopt the Gender Early Warning System (GEWS) approach as an innovative, joint and proactive approach for dealing with emerging trends and incidents of violence against civilians in Nigeria in line with ‘Leave No One Behind Principle’ of the 2030 Agenda of the United Nations.